An efficient authentication and key-distribution protocol for wireless multimedia sensor network - Basavaraj Patil; Sangappa Ramachandra Biradar (Institute of Advanced Engineering and Science, 2022)
To provide security and privacy for multimedia data transmission, efficient techniques for authorizing and authenticating network users and nodes are required. These challenges have made it a vital and significant area of research in the present decade. Du e to resource constraints, existing systems are unable to provide adequate protection against vulnerable behaviors and security assaults such as black-hole, Sybil, man-in-the-middle, and other similar attacks. In this paper, an effective enhanced engineere d cementitious composites (ECC) and crypto-based authentication with a key exchange mechanism is proposed. The method boosts the effective authentication mechanism and reduces the number of vulnerable activities in the network. The simulation results demon strate that the suggested technique is robust to malicious assaults and performs mutual authentication efficiently. A cost-benefit analysis validates that the processing, communication, and storage requirements are much reduced when compared to existing ap proaches. Furthermore, an informal security analysis demonstrates that the suggested protocol is secure and adaptable to real-time scenarios.